2012
DOI: 10.1523/jneurosci.2213-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Corelease of Dopamine and GABA by a Retinal Dopaminergic Neuron

Abstract: Numerous neurons release two transmitters of low molecular mass, but it is controversial whether they are localized within the same synaptic vesicle, with the single exception of GABA and glycine because they are ferried into the vesicle by the same transporter. Retinal dopaminergic amacrine (DA) cells synthesize both dopamine and GABA. Both transmitters are released over the entire cell surface and act on neighboring and distant neurons by volume transmission, but, in addition, DA cells establish GABAergic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…For instance, glutamate and GABA co-neurotransmission has been reported in epilepsy models within mossy fiber terminals (Gutiérrez et al, 2003, Gutiérrez 2003, 2005; Trudeau & Gutiérrez , 2007; Münster-Wandowski et al, 2013), developing medial trapezoid body terminals from the lateral superior olive (Gillespie et al 2005; Noh et al, 2010), entopeduncular nucleus projection to the LHb (Shabel et al, 2014), and cortex (Fattorini et al, 2015). In addition, there is evidence for GABA and DA co-transmission in by substantia nigra pars compacta neurons as well as retinal amacrine neurons (Tritsch et al 2012; Hirasawa et al, 2012). Other forms of neurotransmission include GABA and histamine by hypothalamic neurons (Yu et al, 2015), glutamate and acetylcholine co-transmission in striatal interneurons or medial habenula neurons (Gras et al, 2008; Ren et al, 2011; Higley et al, 2011; Nelson et al, 2014), GABA and acetylcholine co-transmission in corticopetal globus pallidus neurons (Saunders et al, 2015).…”
Section: Cellular Diversity In the Ventral Tegmental Areamentioning
confidence: 99%
“…For instance, glutamate and GABA co-neurotransmission has been reported in epilepsy models within mossy fiber terminals (Gutiérrez et al, 2003, Gutiérrez 2003, 2005; Trudeau & Gutiérrez , 2007; Münster-Wandowski et al, 2013), developing medial trapezoid body terminals from the lateral superior olive (Gillespie et al 2005; Noh et al, 2010), entopeduncular nucleus projection to the LHb (Shabel et al, 2014), and cortex (Fattorini et al, 2015). In addition, there is evidence for GABA and DA co-transmission in by substantia nigra pars compacta neurons as well as retinal amacrine neurons (Tritsch et al 2012; Hirasawa et al, 2012). Other forms of neurotransmission include GABA and histamine by hypothalamic neurons (Yu et al, 2015), glutamate and acetylcholine co-transmission in striatal interneurons or medial habenula neurons (Gras et al, 2008; Ren et al, 2011; Higley et al, 2011; Nelson et al, 2014), GABA and acetylcholine co-transmission in corticopetal globus pallidus neurons (Saunders et al, 2015).…”
Section: Cellular Diversity In the Ventral Tegmental Areamentioning
confidence: 99%
“…Further experiments supported the conclusion that upon GABA exocytosis, the transmitter diffused from the site of release into the surrounding solution and activated nearby native GABA A receptor channels randomly distributed over the plasma membrane of the DA cell. In fact: (i) DA cell perikarya contain organelles stained by antibodies to GABA [22], GAD [45][46][47], synaptobrevin 2 (VAMP2 [26]) and VGAT [48].…”
Section: Extrasynaptic Release Of Dopamine and Gabamentioning
confidence: 99%
“…The question therefore arose whether in DA cells the two transmitters were stored within the same or separate organelles. To solve this problem, we used two approaches: (i) we combined patch-clamp and amperometry in simultaneous recordings of dopamine and GABA release from the same isolated DA cell body and (ii) we used immunocytochemistry with both confocal and electron microscopes to investigate the co-localization of VMAT2 and VGAT in cryosections of the mouse retina [48]. We observed that a proportion of the GABAergic and amperometric dopamine oxidation events appeared to coincide in time, and we generated a perievent time histogram by measuring the time intervals between GABAergic events and the immediately preceding and following dopaminergic events.…”
Section: Co-release Of Dopamine and Gabamentioning
confidence: 99%
“…Nevertheless, neurons with markers or functional evidence suggesting a dual GABAergic/cholinergic phenotype are found, for example, in C. elegans , birds, and the mammalian retina[48]. Furthermore, in zebraf¡sh, catecholamine-producing neurons likely release GABA or glutamate [9], and DANs in mammalian retina and olfactory bulb also appear to be GABAergic [10,11]. The examples presented here therefore highlight common motifs shared across species and brain areas.…”
Section: Introductionmentioning
confidence: 99%